Tai textiles in the Mekong region continuity and change - Connors, Mary F. 1939-; Bao tang d?an toc hoc Viet Nam.; Yunnan min zu xue yuan. Min zu bo wu guan. ([Hanoi] Vietnam Museum of Ethnology, 2006)
Catalog of an exhibition that began at Vietnam Museum of Ethnology on Dec. 10, 2004, and opened at the Yunnan Nationalities Museum in Sept. 2006.
Includes bibliographical references (p. 163).
Keywords: Textile fabrics, Tai -- Mekong River Region -- Exhibitions; Tai (Southeast Asian people) -- Clothing -- Exhibitions; Clothing and dress -- Mekong River Region -- Exhibitions; Mekong River Region -- Social life and customs -- Exhibitions